(untitled) (Indian Journal of Arid Horticulture, 2025)
Due to rising cost of chemical fertilizers and their adverse effects on soil health, the economically attractive and alternate potential sources of plant nutrients should be exploited. The excessive use of these chemical fertilizers adversely affects human health resulting in dreadful diseases like cancer, hypertension and other abnormalities. Further, to sustain the productivity, the bio-inoculants can supplement them to certain extent in various food crops. But it is not the common practice in various horticultural crops. The seed coat of most of the fruit crops is very hard. To break the seed dormancy, either some chemical treatment or long incubation period is required. These bio- inoculants can be helpful in breaking the seed dormancy by producing various plant growth substances. Hence the present investigations were undertaken to study the response of different bio-inoculants in combination with either FYM or vermicompost on seed germination and plant growth in guava (Psidium guajava Lamk.).